2022
DOI: 10.52429/selju.v5i1.690
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis on Efl Students’ Essay Writing (Fourth Semester Students of STMIK Sinar Nusantara Surakarta)

Abstract: This research was finding out the errors made by English Foreign Language students in the essay writing using James' error analysis. This study was qualitative descriptive research with 30 respondents. The data were collected by students' mini research report which was then analyzed by observation and classification using Corder's algorithm. It basically consists of three major stages: recognition, description, and explanation. Finally, the result was classified by using James' four grammatical error categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…On the other side, the learners of English native are difficult to master the second person pronouns either plural and singular, nominative or accusative because they are expressed with different pronominals. Pravitasari's quantitative study concerns various errors made by fourth-semester students of STMIK Surakarta found in their essay writing (Pravitasari, 2022). Most of the errors tend to be influenced by the structure of the student's mother tongue with which they are more fluent.…”
Section: Previous Studiesmentioning
confidence: 99%
“…On the other side, the learners of English native are difficult to master the second person pronouns either plural and singular, nominative or accusative because they are expressed with different pronominals. Pravitasari's quantitative study concerns various errors made by fourth-semester students of STMIK Surakarta found in their essay writing (Pravitasari, 2022). Most of the errors tend to be influenced by the structure of the student's mother tongue with which they are more fluent.…”
Section: Previous Studiesmentioning
confidence: 99%